Spatial Mapping for Managing Oxidized Pyrite (FeS2) in South Sumatra Wetlands, Indonesia - M. Edi Armanto (Journal of Wetlands Environmental Management, 2014)
The research aimed to analyze spatial mapping for managing oxidized pyrite (FeS2) in South Sumatra wetlands, Indonesia. The field observations are done by exploring several transect on land units. The field description refers to Soil Survey Staff (2014). Water and soil samples were taken from selected key areas for laboratory analysis. The vegetation data was collected by making sample plots (squares method) placed on each vegetation type with plot sizes depending on the vegetation type, namely 10 x 10 m for secondary forests and 5 x 5 m for shrubs and grass. The observations of surface water level were done during the river receding with units of m above sea level (m asl). The research results showed that pyrite formation is largely determined by the availability of natural vegetation as Sulfur (S) donors, climate and uncontrolled water balance and supporting fauna such as crabs and mud shrimp.Â  Climate and water balance as well as supporting faunas is the main supporting factors to accelerate the process of pyrite formation. Oxidized pyrite serves to increase soil acidity, becomes toxic to fish ponds and arable soils, plant growth and disturbing the water and soil nutrient balances. Oxidized pyrite is predominantly accelerated by the dynamics of river water and disturbed natural vegetation by human activities.Â  The pyrite oxidation management approach is divided into three main components of technologies, namely water management, land management and commodity management.